(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Assistive mobility devices play a key role in improving the mobility and quality of life of persons with disabilities, ensuring independence, comfort and quality of life. The article highlights the importance of assistive mobility devices in physical rehabilitation, analyzes the role of assistive devices in the rehabilitation process, their impact on the social integration of persons with disabilities and increasing their level of autonomy. Their significance, types and need in the present are presented. The classification of assistive mobility devices is considered. Methods for selecting an assistive device for the parameters and needs of a person are proposed. The role of training for the correct method of movement using the selected device is determined. Special attention is paid to the criteria for choosing the appropriate device depending on the needs of the user, his physical capabilities and level of activity. The availability of assistive technologies in Ukraine is analyzed and solutions are provided to improve the quality of physical rehabilitation services, improve access to assistive devices. Special attention is paid to the correct selection of an assistive device, the need for training and support in the further use of the assistive device. Key factors for improving the quality of life of people with lower limb injuries at home and in society are identified. The prospects of the state in implementing measures to provide access to high-quality assistive technologies for everyone in need, their financing and state support are considered. The article presents the main stages in physical rehabilitation for a person to receive an assistive device in accordance with his needs and purpose, describes the goal and objectives, the main requirements for the selection and further use, training and support of an assistive device.